PENGARUH UKURAN KINERJA ROA, ROE, EPS DAN EVA TERHADAP RETURN SAHAM - Iwin Arnova (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2016)
Iwin Arnova; This study aimed to determine the effect of Return on Assets, Return on Equity, Earnings Per Share, and Economic Value Added to stock return. This study is still condicted regards  different  result  of  various  research.  The  research  was  conducted  using  secondary  data.  The population in this study are all manufacturing companies listed on the Indonesia Stock Exchange (IDX) of the year 2008-2011. The sampling method applies purposive sampling technique. On 48  samples. The data is analysis uses multiple regression analysis. The results of the regression analysis showed that the return on assets have a positive and significant effect on stock returns.  Return on Equity and Earnings Per Share has no effect on stock returns, while the Economic Value Added negatively affect, stock returns. Adjusted R Square value is 0.989, it can be condud 98.9% variable Return on Assets, Return on Equity, Earnings Per Share, and Economic Value Added can be  explained  by  the  variable  stock  returns  while  the  remaining  1.1%  is  explained  by  other variables.